Parotid fistula due to iatrogenic parotid duct injury - Kagali, Nagaraj A.; Latha, G. A. (International Journal of Research in Medical Sciences, 2017)
The most common cause of parotid fistula is trauma, operative complications followed by malignancy and infection. Injury to the duct may be difficult to diagnose unless one has high index of suspicion while operating in the parotid region. Sequelae of inadequate diagnosis and treatment include parotid fistula and sialocele formation which are inconvenient for the patient and difficult to treat. We are reporting a case of parotid fistula due to injury to parotid duct following extensive debridement for necrotising fasciitis of cheek extending to the neck following tooth extraction.